Analysis of the dynamics of a switched circuit from the bifurcation theory. (November 2020) - González, J R; Rivas, E; Correa, G
Abstract: This document shows an analysis of the stability of a Buck type power converter, which, being a switched electronic circuit, has complex dynamics. The analysis consists of determining the influence on its stability of the variations of each of its parameters and determining the points where these changes occur, known as the bifurcation point. This analysis allows investigating these types of problems from the bifurcation theory allowing to understand the stability and operation of the converters.